How can we help you today?
< All Topics
Print

Grade 10 Exercise 4.R.1
(1)a.$\begin{align}\\[5pt]
&2\times 3a\\[5pt]
=&\underline{\underline{6a}}\end{align}$
b.$\begin{align}\\[5pt]
&4\times (-2x)\\[5pt]
=&\underline{\underline{-8x}}\end{align}$
c.$\begin{align}\\[5pt]
&(-3)\times 2x\\[5pt]
=&\underline{\underline{-6x}}\end{align}$
d.$\begin{align}\\[5pt]
&2x\times 3y\\[5pt]
=&\underline{\underline{6xy}}\end{align}$
e.$\begin{align}\\[5pt]
&3a\times (-5b)\\[5pt]
=&\underline{\underline{-15ab}}\end{align}$
f.$\begin{align}\\[5pt]
&(-2m)\times 4n\\[5pt]
=&\underline{\underline{-8mn}}\end{align}$
g.$\begin{align}\\[5pt]
&(-4p)\times (-2q)\\[5pt]
=&\underline{\underline{8pq}}\end{align}$
h.$\begin{align}\\[5pt]
&3x\times 5x\\[5pt]
=&\underline{\underline{15x^2}}\end{align}$
i.$\begin{align}\\[5pt]
&(-5a)\times 3a\\[5pt]
=&\underline{\underline{-15a^2}}\end{align}$
Grade 10 Exercise 4.R.2
(2)a.$\begin{align}\\[5pt]
&2(x+1)\\[5pt]
=&\underline{\underline{2x+2}}\end{align}$
b.$\begin{align}\\[5pt]
&3(b+3)\\[5pt]
=&\underline{\underline{3b+9}}\end{align}$
c.$\begin{align}\\[5pt]
&4(y-2)\\[5pt]
=&\underline{\underline{4y-8}}\end{align}$
d.$\begin{align}\\[5pt]
&-3(a+2)\\[5pt]
=&\underline{\underline{-3a-6}}\end{align}$
e.$\begin{align}\\[5pt]
&-2(x-2)\\[5pt]
=&\underline{\underline{-2x+4}}\end{align}$
f.$\begin{align}\\[5pt]
&x(2x+3)\\[5pt]
=&\underline{\underline{2x^2+3x}}\end{align}$
g.$\begin{align}\\[5pt]
&2y(y+1)\\[5pt]
=&\underline{\underline{2y^2+2y}}\end{align}$
h.$\begin{align}\\[5pt]
&-2x(4x+1)\\[5pt]
=&\underline{\underline{-8x^2-2x}}\end{align}$
i.$\begin{align}\\[5pt]
&-3b(a-b)\\[5pt]
=&\underline{\underline{-3ab+3b^2}}\end{align}$
j.$\begin{align}\\[5pt]
&2(a-b-3c)\\[5pt]
=&\underline{\underline{2a-2b-6c}}\end{align}$
Grade 10 Exercise 4.R.3
(a)i.$\begin{align}\\[5pt]
&x(x+2)+2(x+2)\\[5pt]
=&x^2+2x+2x+4\\[5pt]
=&\underline{\underline{x^2+4x+4}}\end{align}$
ii.$\begin{align}\\[5pt]
&y(y+3)+3(y-2)\\[5pt]
=&y^2+3y+3y-6\\[5pt]
=&\underline{\underline{y^2+6y-6}}\end{align}$
iii.$\begin{align}\\[5pt]
&x(x+1)-3(x-1)\\[5pt]
=&x^2+x-3x+3\\[5pt]
=&\underline{\underline{x^2-2x+3}}\end{align}$
iv.$\begin{align}\\[5pt]
&m(m-3n)-n(m-3n)\\[5pt]
=&m^2-3mn-mn+3n^2\\[5pt]
=&\underline{\underline{m^2-4mn+3n^2}}\end{align}$
(b)i.$\begin{align}\\[5pt]
&(x+5)(x+8)\\[5pt]
=&x^2+8x+5x+40\\[5pt]
=&\underline{\underline{x^2+13x+40}}\end{align}$
ii.$\begin{align}\\[5pt]
&(7+a)(3+a)\\[5pt]
=&21+3a+7a+a^2\\[5pt]
=&\underline{\underline{21+10a+a^2}}\end{align}$
iii.$\begin{align}\\[5pt]
&(x-5)(x+8)\\[5pt]
=&x^2+8x-5x-40\\[5pt]
=&\underline{\underline{x^2+3x-40}}\end{align}$
iv.$\begin{align}\\[5pt]
&(x+5)(x-8)\\[5pt]
=&x^2-8x+5x-40\\[5pt]
=&\underline{\underline{x^2-3x-40}}\end{align}$
v.$\begin{align}\\[5pt]
&(2+m)(3-m)\\[5pt]
=&6+3m-2m-m^2\\[5pt]
=&\underline{\underline{6+m-m^2}}\end{align}$
vi.$\begin{align}\\[5pt]
&(x-5)(x-8)\\[5pt]
=&x^2-8x-5x+40\\[5pt]
=&\underline{\underline{x^2-13x+40}}\end{align}$

By studying this lesson you will be able to

Expand the squares of a binomial expression. Multiply two binomial expression.

X